Neonatal Sepsis: Clinical Considerations - Blatt, S.; Schroth, M. (Journal of Child Science, 2017)
Unspecific symptoms and rapid development of sepsis up to septic shock from systemic inflammatory response syndrome (SIRS) are well-known, important issues in neonatology. A common cause is the infection by Streptococcus agalactiae (Group B Streptococcus [GBS]) or Escherichia coli, which contributes significantly to neonatal morbidity and mortality. Whereas early-onset sepsis is normally derived from mother during birth, late-onset sepsis can be transmitted by the environment. Management of neonatal sepsis includes the maintenance of cardiovascular and pulmonary function besides antibiotic therapy. Due to the fact that until today, there are no reliable screening tests for detecting early sepsis, clinical assessment is considered to be of utmost importance.
Keywords: neonatal sepsis; late-onset; early-onset; group B Streptococcus; diagnosis